2011
DOI: 10.1038/npp.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

mGluR8 Modulates Excitatory Transmission in the Bed Nucleus of the Stria Terminalis in a Stress-Dependent Manner

Abstract: Metabotropic glutamate receptors (mGluRs) are important modulators of excitatory transmission, and have been implicated in anxiety and stress-related behaviors. Previously, we showed that group III mGluR agonists could depress excitatory synaptic transmission in the bed nucleus of the stria terminalis (BNST), an integral component of the anxiety circuitry. Here, we provide converging evidence indicating that this effect is mediated primarily by mGluR8, is exerted presynaptically, and is modulated by noradrener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…a 1 -AR-Induced Depression of Excitatory Transmission in the dlBNST is Not Blocked by an OX 1 R Antagonist As shown above, orexin A, acting at the OX 1 R, depresses excitatory transmission in the dlBNST. Similarly, previous work in our lab has demonstrated that several other Gq-linked receptors (eg, a 1 -AR, mGluR1, mGluR5) cause a depression of excitatory transmission in the dlBNST (Gosnell et al, 2011;Grueter et al, 2006;McElligott et al, 2010;Winder, 2008, 2009). Although the a 1 -AR antagonist prazosin did not block yohimbine-induced depression of excitatory transmission (see above), to further address possible activation of common downstream effectors, we investigated if an OX 1 R antagonist could block methoxamine (a Gq-linked a 1 -AR)-induced depression in the dlBNST.…”
Section: Yohimbine-induced Depression Of Excitatory Transmission In Tsupporting
confidence: 74%
“…a 1 -AR-Induced Depression of Excitatory Transmission in the dlBNST is Not Blocked by an OX 1 R Antagonist As shown above, orexin A, acting at the OX 1 R, depresses excitatory transmission in the dlBNST. Similarly, previous work in our lab has demonstrated that several other Gq-linked receptors (eg, a 1 -AR, mGluR1, mGluR5) cause a depression of excitatory transmission in the dlBNST (Gosnell et al, 2011;Grueter et al, 2006;McElligott et al, 2010;Winder, 2008, 2009). Although the a 1 -AR antagonist prazosin did not block yohimbine-induced depression of excitatory transmission (see above), to further address possible activation of common downstream effectors, we investigated if an OX 1 R antagonist could block methoxamine (a Gq-linked a 1 -AR)-induced depression in the dlBNST.…”
Section: Yohimbine-induced Depression Of Excitatory Transmission In Tsupporting
confidence: 74%
“…Consistent with this, mGlu 8 KO mice display deficits in hippocampal-dependent learning [219]. Additionally, mGlu 8 suppresses glutamatergic input into the bed nucleus of the stria terminalis (BNST) implicating a role for this receptor in anxiety and stress [220], consistent with results observed in the mGlu 8 KO mice [221]. Similar to both mGlu 4 and mGlu 7 , the neuromodulatory role of mGlu 8 in brain regions implicated in learning and memory suggests that mGlu 8 ligands could be beneficial in treating the cognitive deficits in patients with schizophrenia.…”
Section: Group III Mglu Receptors (Mglu4 Mglu7 and Mglu8)mentioning
confidence: 88%
“…Although genetic variations of GRM8 in schizophrenia and the antipsychotic effects of mGluR8 agonists have been inconsistently reported in the literature [71, 72, 73, 74], there are conclusive reports regarding its role in mediating excitatory transmission in response to environmental stressors. In fact, the mGlu8 receptor has been specifically implicated in anxiety and stress-related behaviors and its activation has been shown to produce strong anxiolytic effects [75, 76]. Thus, the observed increase in its expression might represent another adaptive response in SLC1A1 deletion carriers, thereby helping them to deal better with stressful stimuli or events.…”
Section: Discussionmentioning
confidence: 99%